BUILDING THE ETHIC OF MORALITY OF TEACHERS AND STUDENTS USING “AL-ASMA AL-HUSNA” AS A BASIS TO REFORM EDUCATION IN THE GLOBALIZATION ERA - Alfan, Muhammad; Arrumawan, Muhammad Muhsin (Proceeding of International Conference on Islamic Education (ICIED); Vol 3 No 1 (2018): Proceeding of International Conference on Islamic Education (ICIED), 2018)
This paper is written with the title Building the Ethic of Morality of Teachers and Students Using “ al- Asma al- Husna ” as A Basis to Reform Education in The Globalization Era. The aim of this paper is offering al-Asma al-Husna to be used by educators and students as moral ethics and morally in this challenging global era. This study uses a literature review and qualitative methods. Then the research data was analyzed using descriptive methods. The data in this study are information related to topics that come from relevant scientific article books. The findings of this paper are there several educational institutions, both formal and non-formal have placed al-Asma al-Husna in a position parallel to Pancasila and even higher. A l-Asma al-Husna is used as a code of ethics for school residents, especially educators and students. Writers found this very noble phenomenon in various educational institutions in Malang, such as in the Anak Saleh Elementary School, MIN Malang I, MTsN Malang I, MAN 2 Malang, Miftahul Huda Islamic Boarding School, UIN Malang, and so on. To realize the code of ethics of al-Asma al-Husna , the educational institution follows the following methods: 1) Understanding al-Asma al-Husna in lesson 2) Memorizing al-Asma al-Husna with beautiful songs and intonation 3) Say al-Asma 'al-Husna before starting and ending the lesson 4) Launching the song al-Asma al-Husna at the flag ceremony every Monday before singing the song Indonesia Raya 5) a l-Asma al-Husna echoing every activity. That is way al-Asma al-Husna and the meaning contained in it can truly be felt in the conscience of teachers and students as the main subject of education. And in the end, al-Asma al-Husna can be made an absolute code of ethics that has been agreed upon